Analysis of Eremostachys hyoscyamoides essential oil composition and assessing the antibacterial and antioxidant properties of the ethanol extract - Marjan Talebi; Afsaneh Arefei Oskouie; Arash Mahboubi; Mohammad Khani; Faraz Mojab (Heliyon)
The increasing issue of antibiotic resistance in bacterial infections has led to challenging and costly treatments. Free radicals significantly contribute to the progression of several diseases, such as cardiometabolic disorders, neurodegenerative conditions, and cancers. Antioxidants can help alleviate or prevent these health problems. This research aimed to assess the antibacterial and antioxidant effects of Eremostachys hyoscyamoides ethanol extract. Additionally, the chemical profile of the essential oil obtained from the aerial parts of E. hyoscyamoides was characterized through gas chromatography-mass spectrometry (GC-MS). The extract's antibacterial effect was tested against three Gram-positive bacteria (Micrococcus luteus, Staphylococcus epidermidis, and S. aureus), in addition to three Gram-negative bacteria (Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli). The cup-plate method was employed to assess the antibacterial activity, which was subsequently followed by the determination of the minimum inhibitory concentration through the agar dilution method. To evaluate the antioxidant effects, the DPPH radical scavenging assay was used. The total phenolic content (TPC) and flavonoid content (TFC) of the extract were quantified using the Folin Ciocalteu and Aluminum Chloride methods as spectrophotometric-based techniques, respectively. The essential oil of E. hyoscyamoides was extracted via hydrodistillation and subjected to GC-MS analysis. The findings demonstrated that the ethanol extract of E. hyoscyamoides effectively inhibited the growth of the bacterial strains examined. The IC50 value measured in the DPPH test was 48.194 ± 0.61 μg/mL. The TPC was found to be 84.15 ± 2.5 mg GAE/g, while the TFC was determined to be 19.35 ± 1.3 mg RE/g. A total of 50 components, accounting for 93.6 % of the essential oil composition, were identified. High concentrations of elemol (6.8 %), 2,4-di-tert-butylphenol (10.7 %), and linalyl acetate (4.2 %) were putatively identified in the essential oil. In conclusion, the ethanol extract of E. hyoscyamoides exhibited hopeful potential as a natural source of antioxidants and antibacterial agents.